Getting Real in the Classroom. - Van Genuchten, Michiel; Vogel, Doug (Computer (00189162), 2007)
The article discusses an educational endeavor that lets computer science students experience the scope and complexity of large, real-life software projects. The BOHKNet project lasts for eight weeks and involves teams of students from several countries and universities. Teams must collaborate via videoconferencing, email, and learning-management software on a project whose demands require that they cope with joint planning, the breaking down of complicated tasks into smaller ones and delegation of same, information overload, and knowledge management.